2009
DOI: 10.1348/096317908x360693
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of instructor behaviours and their relationship to leadership

Abstract: This study analysed qualitatively the nature of instructor behaviours and their relationship to leadership. The Critical Incident Technique was used to collect effective and ineffective incidents of instructor behaviour in military training from both instructors' and trainees' perspectives (total incidents ¼ 1150, effective ¼ 696, ineffective ¼ 494), across the three UK Armed Services. Nine dimensions of instructor behaviour were developed with high inter-and intra-coder reliability. No differences were found … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
14
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 58 publications
3
14
0
Order By: Relevance
“…The mass media invariably castigate as “bad role models” elite athletes found to have acted in a socially disapproved of manner (usually involving drugs, sex, or cheating). Role models are also associated with leadership (e.g., Dirks & Ferrin, 2002; Patrick, Scrase, Ahmed, & Tombs, 2009). Few would argue that the young do not tend to imitate and otherwise learn from those whom they admire.…”
Section: Attention Attractors As Exaptationsmentioning
confidence: 99%
“…The mass media invariably castigate as “bad role models” elite athletes found to have acted in a socially disapproved of manner (usually involving drugs, sex, or cheating). Role models are also associated with leadership (e.g., Dirks & Ferrin, 2002; Patrick, Scrase, Ahmed, & Tombs, 2009). Few would argue that the young do not tend to imitate and otherwise learn from those whom they admire.…”
Section: Attention Attractors As Exaptationsmentioning
confidence: 99%
“…Interestingly, a more recent study by Patrick, Scrase, Ahmed, and Tombs (2009) conducted in a military context found five categories of effective instructor behaviors that mirror the findings of Blasé and Blasé (2000). The effective leadership behaviors among leaders of the United Kingdom's armed forces included "showing and demonstrating; encouraging behaviours, using instructional strategies, feedback, practice and adapting;…”
Section: Teachers and The Instructional Leadership Experiencesupporting
confidence: 59%
“…We identified incidents based on three criteria (cf. Butterfield et al, 2005; Patrick, Scrase, Ahmed, & Tombs, 2009). Incidents had to involve (a) specific behavior of employment counselors, (b) a specific episode, and (c) behavior with a positive or negative effect on helping people find a job.…”
Section: Resultsmentioning
confidence: 99%
“…In the second substep, three raters (the first and fourth authors and an experienced psychologist not familiar with the aim of the study) independently classified all 539 incidents into the category framework. This procedure represents an external validation of the framework, a step that is often omitted in CIT studies (Patrick et al, 2009). The three raters also allocated incidents that they believed did not fully describe specific behavior or were beyond the scope of the study to the undefined category.…”
Section: Content Data Analysis and Developing A Category Frameworkmentioning
confidence: 99%